2018
DOI: 10.1186/s13256-017-1528-4
|View full text |Cite
|
Sign up to set email alerts
|

Atrial septal defect in a patient with congenital disorder of glycosylation type 1a: a case report

Abstract: BackgroundAtrial septal defect often become more severe when encountered in genetic syndromes. Congenital disorder of glycosylation type 1a is an inherited metabolic disorder associated with mutations in PMM2 gene and can affect almost all organs. Cardiac abnormalities vary greatly in congenital disorder of glycosylation type 1a and congenital heart defects have already been reported, but there is little knowledge about the effect of this inherited disorder on an existing congenital heart defect. Herein we rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 13 publications
(16 reference statements)
1
5
0
Order By: Relevance
“…Our study confirmed previously reported infection-related features in PMM2-CDG, namely (1) the higher prevalence of infections during infancy/early childhood; (2) their organ-specific pattern (particularly RT and GI); (3) the not negligible occurrence of sepsis evolving from organ-specific infections and iv) their associated early lethality [13,14,16,17,52,53]. All these observations highlight the need for close monitoring until full remission occurs to ensure recovery and to prevent clinical aggravation and fatal outcomes [17].…”
Section: Discussionsupporting
confidence: 90%
“…Our study confirmed previously reported infection-related features in PMM2-CDG, namely (1) the higher prevalence of infections during infancy/early childhood; (2) their organ-specific pattern (particularly RT and GI); (3) the not negligible occurrence of sepsis evolving from organ-specific infections and iv) their associated early lethality [13,14,16,17,52,53]. All these observations highlight the need for close monitoring until full remission occurs to ensure recovery and to prevent clinical aggravation and fatal outcomes [17].…”
Section: Discussionsupporting
confidence: 90%
“…There are reports showing ASD as very severe when associated with genetic syndromes. Wu et al presented a case of 10 mm ASD in an 8 month-old male infant with congenital disorder of glycosylation [8]. In our patient, there was no dysmorphism or features suggestive of any inborn error of metabolism.…”
Section: Online Firstmentioning
confidence: 47%
“…Patient demographics, diagnoses, and symptoms are presented in Tables 1 and 2. From 960 patients described in the literature, 14 had reported CHD 10‐19 . The most common form of CHD in the patients of our literature review was tetralogy of Fallot (TOF) (5/14 patients, 35.7%), followed by persistent ductus arteriosus (PDA) (3/14, 21.4%) and truncus arteriosus (3/14, 21.4%).…”
Section: Methodsmentioning
confidence: 99%